Thermoresponsive polymers: From natural proteins to amino acid based polymer synthesis - Badreldin, Mostafa; Salas-Ambrosio, Pedro; Garanger, Elisabeth; Lecommandoux, Sébastien; Harrisson, Simon; Bonduelle, Colin (Progress in polymer science, 2023)
In polymer science, thermoresponsiveness refers to macromolecular systems that display a marked and discontinuous change in their physical properties with temperature. Such smart polymers are the focus of increasing attention as they provide new solutions to many applications (e.g., drug delivery, nanotechnology, tissue engineering and biotechnology). This review focuses on amino acid based polymers, mainly synthetic polypeptides that are obtained by ring-opening polymerization. These include polymers based on natural amino acids, synthetic or modified amino acids and N-alkylated glycine derivatives. Based on what is known about the behavior of natural proteins in response to temperature variations, this review provides a comprehensive overview of the state of the art of thermosensitive polypeptides through a detailed description i) of the structure/thermoresponsiveness relationship, ii) of the mechanisms involved at the molecular level, iii) of their possible applications both in materials science and in biomedical applications.